Examination of Factors that Lead to Rent Default on Selected Residential Properties in Awka, Anambra State - J. C., Onyejiaka; C. N., Onyima; J. I., Okafor (International Journal of Real Estate, 2025)
Rent is a return expected from real estate investment. This can flow annually or monthly. Rent default is non-payment of rent by the tenant to the property owner as at when due. This directly or indirectly will affect the goal of the investment. It is the aim of this study to examine factors that lead to rent default in residential properties in Awka, Anambra state. The research adopted the field survey approach and made use of interviews, personal discussions and well-structured questionnaires as its instrument of data collection. Questionnaires were distributed to practicing Estate Surveyors and Valuers in Awka, practicing lawyers in Awka and tenants of 10 selected 2-storey residential properties of which a total of 273 questionnaires were distributed and 248 were retrieved. The data collected were duly presented in tables and analyzed using frequency, percentage and simple mean. The study revealed that rent default in residential properties in Awka metropolis, Anambra State is as a result of bad economic condition of the country, lack of proper management of the property and unforeseen circumstances. Selection of suitable tenants and proper management of residential properties could reduce the menace of rent default in the study area. Installment payment of subsequent rent should be allowed so as to enable the tenant pay the rent with ease.